Opportunistic diseases in marine eukaryotes: Could Bacteroidota be the next threat to ocean life?. (4th August 2022) - Hudson, Jennifer; Egan, Suhelen
Abstract: Bacteria within the phylum Bacteroidota (Bacteroidetes) are known to cause devastating and widespread disease outbreaks in marine eukaryotic hosts. However, with few pathogens described in detail, their prevalence and virulence strategies remain largely unknown. Here, we systematically reviewed the literature to evaluate the current understanding of Bacteroidota that cause disease in marine hosts. Isolates affiliated with the genera Tenacibaculum and Aquimarina (Flavobacteriaceae) were the most widely reported and characterized pathogens. Although cultured isolates were predominantly Flavobacteriia, culture‐independent studies also found classes Bacteroidia, Cytophagia and Sphingobacteriia associated with disease. We found that pathogenic marine Bacteroidota largely conformed to an opportunistic lifestyle but could also act as secondary pathogens or were involved in polymicrobial diseases. Many diseases were also associated with an environmental stressor, especially those affecting coral, macroalgae and fish. Key virulence traits included the production of adhesins and host tissue‐degrading enzymes. Overall, the nature of disease involving Bacteroidota pathogens appears to be an outcome of complex host–pathogen–environment interactions; however, our understanding of virulence remains limited by the lack of functional characterization studies. This is concerning as Bacteroidota have the potential to emerge as a serious threat to marine ecosystems and aquaculture industries, driven by global changes in ocean conditions.